Tree genotype and genetically based growth traits structure twig endophyte communities1. Issue 3 (1st March 2014) - Lamit, Louis J.; Lau, Matthew K.; Sthultz, Christopher M.; Wooley, Stuart C.; Whitham, Thomas G.; Gehring, Catherine A.
Abstract : Premise of the study: Fungal endophytes asymptomatically inhabit plant tissues where they have mutualistic, parasitic, or commensal relationships with their hosts. Although plant–fungal interactions at the genotype scale have broad ecological and evolutionary implications, the sensitivity of endophytes in woody tissues to differences among plant genotypes is poorly understood. We hypothesize that (1) endophyte communities in Populus angustifolia (Salicaceae) twigs vary among tree genotypes, (2) endophyte variation is linked to quantitative tree traits, and (3) tree genotype influences interspecific fungal interactions. Methods: Endophytes were isolated from twigs of replicated P. angustifolia genotypes in a common garden and characterized with PCR‐RFLP and DNA sequencing. Twig length and diameter, aboveground tree biomass, and condensed tannins were also quantified. Key results: (1) Aspects of fungal community structure, including composition and total isolation frequency (i.e., abundance), varied among genotypes. (2) Aboveground biomass and twig diameter were positively associated with isolation frequency and covaried with composition, whereas twig length and condensed tannin concentration were not significantly correlated to endophytes. (3) Fungal co‐occurrence patterns suggested negative species interactions, but the presence of significant co‐occurrences was genotype dependent. Conclusions: The species is often assumed to be the most important ecological unit; however, these results indicate that genetically based trait variation within a species can influence an important community of associated organisms. Given the dominance of plants as primary producers and the ubiquity of endophytes, the effect of host genetic variation on endophytes has fundamental implications for our understanding of terrestrial ecosystems.